Plastic yielding of glass in high‐pressure torsion apparatus. (19th September 2018) - Ding, Linfeng; Kerber, Michael; Kunisch, Clemens; Kaus, Boris J. P.
Abstract: Hardness measurements performed at room temperature have demonstrated that glass can flow under elevated pressure, whereas the effect of high pressure on glass rheology remains poorly quantitated. Here, we applied a high‐pressure torsion apparatus to deform SCHOTT SF6 ® glass and attempted to quantitate the effect of pressure and temperature on the shear deformation of glass subjected to pressures from 0.3 to 7 GPa and temperatures from 25 to 496°C. Results show that the plastic yield deformation was occurring during the HPT experiments on the SF6 glass at elevated temperature from 350 to 496°C. The yield stress of SF6 glass decreases with increasing temperature and decreasing pressure. An extended Arrhenius model with one set of parameters, namely infinite yield stress Y 0 = 0.17 ± 0.1 GPa, activation energy E a = 4.8 ± 0.5 kJ/mol and activation volume V a = 1.4 ± 0.2 cm 3 /mol, can explain the experimental results well.